On the role of diagnosis of prostate diseases at the outpatient appointment of a therapist - A. L. Kebina; A. S. Sycheva; A. L. Vertkin; G. Yu. Knorring (Лечащий Врач)
Malignant diseases remain an important problem in medicine, while its solution depends on the effectiveness of detecting the early stages of cancer at the outpatient stage, including the therapeutic link in the provision of medical care. Currently existing approaches to the promotion of the foundations of a healthy lifestyle are mainly aimed only at the prevention of behavioral risk factors: tobacco smoking, unhealthy diet, insufficient physical activity and harmful use of alcohol. At the same time, according to experts, even exposure only to them will prevent at least 40% of cases of the development of malignant ovariances. A 3-tier system of medical care has been organized in Russia. It is the first level of primary health care that should ensure the prophylactic focus of health care: competent clinical examination is able to provide a significant, up to 30%, contribution to reducing the overall mortality of the population, including mortality from malignant neoplasms. The first stage in the diagnosis of oncological disease are therapists, to whom patients come with general complaints (fatigue, low-grade fever, joint pain, dysuria, etc.). The most urgent task in the work of a general practitioner is the timely detection of a tumor disease and referral of a patient for treatment to an oncologist. The article considers the possibilities of screening measures with the participation of therapists, general practitioners, and offers specially developed algorithms for the diagnosis of benign and malignant neoplasms of the prostate gland. The formation of oncological alertness skills in a primary outpatient care physician is necessary for early detection and reduction of the incidence of advanced stages of tumors and earlier initiation of specialized treatment. Identification of symptoms suspicious of malignant neoplasms using algorithmic approaches and subsequent consultation with the patient by a specialist urologist or oncologist should improve treatment outcomes.